2008
DOI: 10.25011/cim.v31i1.3135
|View full text |Cite
|
Sign up to set email alerts
|

The effects of renal replacement therapy on plasma, asymmetric dimethylarginine, nitric oxide and C-reactive protein levels

Abstract: Clin Invest Med 2008; 31 (1): E1-E7. AbstractPurpose: Asymmetric dimethylarginine (ADMA), nitric oxide (NOx), and C-reactive protein (CRP) are important risk factors for endothelial dysfunction and mortality in the end stage renal diseases population. The aim of the study was to investigate the relationship between renal replacement therapy and endothelial dysfunction. Methods: Plasma NOx, ADMA and CRP levels were examined in randomized selected 30 patients with chronic kidney diseases (CKD), 28 patients recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
2
9
0
1
Order By: Relevance
“…In these studies, patients with renal impairment had elevated plasma NOx levels. These data are not unchallenged as some other studies report that NOx remains unchanged or even declines in renal failure . Moreover, net endogenous NOx generation may actually be lower in renal failure .…”
Section: Discussionmentioning
confidence: 61%
“…In these studies, patients with renal impairment had elevated plasma NOx levels. These data are not unchallenged as some other studies report that NOx remains unchanged or even declines in renal failure . Moreover, net endogenous NOx generation may actually be lower in renal failure .…”
Section: Discussionmentioning
confidence: 61%
“…This result is consistent with the previous similar studies in the literature regarding ADMA levels in ESRD patients (9,14,15). Circulating levels of ADMA had a positive correlation with levels of CRP.…”
Section: Discussionsupporting
confidence: 83%
“…In previous studies, ADMA levels were found to be higher in ESRD patients both on peritoneal dialysis and hemodialysis (HD) compared with healthy controls (8,9). Increased levels of ADMA are thought to be associated with the increased frequency of cardiovascular events seen in ESRD patients (10,11), and it is suggested that ADMA might be a novel cardiovascular risk factor for both ESRD patients and the general population (7,12).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, plasma inflammation markers, such as CRP and fibrinogen, are elevated in predialysis and HD patients (44). In particular, CRP represent an important risk factor for endothelial dysfunction and mortality in the ESRD population, not significantly modified by administration/supplementation of antioxidant substances (45).…”
Section: Discussionmentioning
confidence: 99%